Production, purification and characterization of a proteolytic enzyme from Streptomyces sp. 2M21. Issue 5 (3rd September 2019) - Deniz, Irem; Zihnioglu, Figen; Öncel, Suphi S.; Hames, E. Esin; Vardar-Sukan, Fazilet
Abstract: The recent application studies on keratinase lead to new application areas for the enzyme to be used in novel industries such as pharmaceuticals and biodegradable composites. Thus, designing an economical and environmentally friendly keratinase production and purification with new features turned into an intriguing objective for its commercialization. In this study, keratinase enzyme was produced using a bioreactor of 5 L by a native Streptomyces sp. 2M21 and purified by ion exchange chromatography using step-wise gradient with 24.1-fold purification. Purified keratinase showed optimum activity at pH 9 and 30 °C. The enzyme was shown to be able to decompose different complex substrates such as chicken feather, wool and nail. Moreover, the addition of DTT enhanced the hydrolysis of wool and chicken feather to 3.4- and 3.2-fold, respectively. The potential of Streptomyces sp. to produce significant levels of keratinase using feathers as a substrate might establish cleaner applications for the production of high value-added products and degrading of keratin-containing wastes.